A Systematic Review of Atypical Teratoid Rhabdoid Tumor in Adults - Chan, Vivien; Marro, Alessandro; Findlay, J. Max; Schmitt, Laura M.; Das, Sumit (Frontiers in Oncology, 2018)
Background: Atypical teratoid/rhabdoid tumor in adults is a relatively rare malignant neoplasm. It is characterized by the presence of rhabdoid cells in combination with loss of either the INI1 or BRG1protein from the tumor cells. Methods: A systematic review was conducted using MEDLINE using the terms ‘atypical teratoid rhabdoid tumor’ AND ‘adult’. The systematic review was supplemented with relevant articles from the references. Cases were included if the pathology was confirmed by loss of INI1 or BRG1. We included a case from our institution. The dataset was analyzed using descriptive statistics and log-rank test. Results: A total of 50 cases from 29 articles were included in this study. The average age at diagnosis was 36.7 years. The most common locations reported are the sellar region and cerebral hemispheres (without deep grey matter involvement). Of the 50 cases, 14 were reported to show evidence of dissemination. The average overall survival was 20 months. There was a significant difference in survival between the adjuvant therapy groups (p=<0.0001). Conclusion: Atypical teratoid rhabdoid tumor of the central nervous system in adults is a rare neoplasm associated with a poor prognosis in a majority of patients. The treatment and clinical course are highly variable, and it remains unclear which factors impact prognosis.